Two improved content extraction signature schemes - Min WANG; Jin-hua MA; Jiang-hua LIU; Wei WU (网络与信息安全学报)
Motivated by the idea of batch signatures,two variants of content extraction signature schemes based on commit vector and RSA respectively were presented.In the proposed schemes,the efficiency of signing and verification were improved by unifying certain message.The analysis show that the proposed schemes are existentially unforgeable under chosen message attacks in the random oracle model.